PEMANFAATAN RPTRA SEBAGAI PUSAT KEGIATAN PENGABDIAN MASYARAKAT - Budi Budi (Jurnal Pengabdian dan Kewirausahaan, 2017)
The Government of Indonesia is committed to respecting and fulfilling the rights of the child. This is reflected in the government's decision to ratify the Convention on the Rights of the Children through Presidential Decree no. 36 of 1990 which was then followed up by the State Ministry of Women's Empowerment through the Regulation of the Minister of State for Women's Empowerment no. 2 of 2009 concerning the Decent Regency / City Children policy (KLA. In 2015, DKI Jakarta Provincial Government targets to build +60 RPTRA in all areas of DKI Jakarta, and +150 other RPTRA in 2016. In the development of RPTRA, the DKI Government uses tripartite development model by involving private parties and universities. Besides the main function as a center for child friendly activities, RPTRA is also expected to be the center of activity and socializing of the surrounding community. As a companion university in the development of RPTRA Dharma Suci, Bunda Mulia University is obliged to assist and coordinate with RPTRA managers so that RPTRA can function as intended. It is lasts from April 2016-December 2016. The methods undertaken in carrying out activities in RPTRA are training, seminars, and counseling. The existence of universities in the utilization of RPTRA turned out to help the utilization of RPTRA maximally, and also increase the benefits of community service activities that are done because the right target and as needed. Therefore, the government of DKI Jakarta is expected to accelerate and increase the existence of RPTRA, and maintain the involvement of universities in filling the community service activities in RPTRA.Keywords: child-friendly integrated public space, RPTRA, Jakarta